Phylogenetic Relationships of Harpyionycterine Megabats (Chiroptera: Pteropodidae) - Giannini, Norberto Pedro (2009)
After almost 70 years of stability following publication of Andersen's (1912) monograph on the group, the systematics of megachiropteran bats (Chiroptera: Pteropodidae) was thrown into flux with the advent of molecular phylogenetics in the 1980s' a state where it has remained ever since. One particularly problematic group has been the Austromalayan Harpyionycterinae, currently thought to include Dobsonia and Harpyionycteris, and probably also Aproteles. In this contribution we revisit the systematics of harpyionycterines. We examine historical hypotheses of relationships including the suggestion by O. Thomas (1896) that the rousettine Boneia bidens may be related to Harpyionycteris, and report the results of a series of phylogenetic analyses based on new as well as previously published sequence data from the genes RAG1, RAG2, vWF, c-mos, cytb, 12S, tVal, 16S, and ND2. Despite a striking lack of morphological synapomorphies, results of our combined analyses indicate that Boneia groups with Aproteles, Dobsonia, and Harpyionycteris in a well-supported, expanded Harpyionycterinae. While monophyly of this group is well supported, topological changes within this clade across analyses of different data partitions indicate conflicting phylogenetic signals in the mitochondrial partition. The position of the harpyionycterine clade within the megachiropteran tree remains somewhat uncertain. Nevertheless, biogeographic patterns (vicariance-dispersal events) within Harpyionycterinae appear clear and can be directly linked to major biogeographic boundaries of the Austromalayan region. The new phylogeny of Harpionycterinae also provides a new framework for interpreting aspects of dental evolution in pteropodids (e.g., reduction in the incisor dentition) and allows prediction of roosting habits for Harpyionycteris, whose habits are unknown.